Spatial analysis of road traffic accident deaths in the state of Paraná, 2007-2016 (Research, Society and Development, 2021)
Brazil is in fifth place among countries with the highest number of land transport accidents. The state of Paraná, Brazil, was the object of this study which conducted spatial analysis with the aim of identifying areas where this phenomenon occurs more and their time series over a 10-year period. This was an ecological and exploratory observational study covering the period 2007 to 2016 in 39 micro-regions of the state of Paraná. Data of road traffic accident deaths as per the International Classification of Diseases (ICD-10, codes V01 to V89) held on the Mortality Information System, were analyzed. Relative risk rates were calculated and choropleth maps were built. A total of 31,651 deaths from the causes examined were recorded according to municipality of occurrence. The most frequent ICD-10 items found were those involving automobile occupants, motorcyclists, pedestrians and cyclists in road traffic accidents. An overall falling trend was found with effect from 2012. The rate by area did not show pronounced spatial dependence and there was considerable variation, whereby the Cerro Azul micro-region had the lowest relative risk in the period, while in Campo Mourão deaths were around 53.3% above the expected level. The estimated average annual trend for the Curitiba micro-region had the steepest fall in the period, while Campo Mourão had the highest rising trend. The trend analysis indicated places where more robust public policy interventions and enforcement actions need to be reviewed.